Pendampingan pembuatan produk makanan olahan durian di Desa Jering Kabupaten Aceh Timur Provinsi Aceh - Septiawan, Muhamad Kiki (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2024)
Hidden paradise on earth Veranda of Mecca from a village called Jering located in Serbajadi District, East Aceh Regency, Nanggroe Aceh Darussalam Province. The average population of Jering Village is a farmer, very rarely open their own business, most open a small grocery store. Every year the village produces the most durian fruit so that it is known as the village that produces the most delicious durian in Serbajadi District. The implementation began in August 2024, and was attended by 14 participants. This activity aims to be an arena for community service that is more useful by assisting in making mochi from durian raw materials in Jering Village, Serbajadi District, East Aceh Regency. We take an approach in this Training using stages, the first stage is explaining the material, the second stage is the process of making durian mochi, the third stage provides space for questions and answers, and the fourth stage evaluates what needs to be improved. Based on the results of interviews with mothers in Jering Village, they did not know about mochi, it was the first time they heard of a food called mochi. In fact, in previous years in Jering Village, durian was flooded and not utilized effectively so that many durians were sold cheaply and eaten just like that. By implementing this assistance, it is hoped that it will have a positive and beneficial impact on MSME business actors so that they have a lot of income during the durian season.